1994
DOI: 10.1007/bf02250990
|View full text |Cite
|
Sign up to set email alerts
|

Infant attachment in a sample of adolescent mothers

Abstract: Thirty-eight, healthy, full-term, first-born infants of adolescent mothers were assessed in a standardized laboratory setting using a modified Ainsworth Strange Situation procedure for assessing attachment. The security rate within this sample was 23.7% which differed considerably from that reported in most white middle class samples of approximately 55-65%. Within this sample, 31.6% were classified as insecure/disorganized which contrasts with 12% in middle class white samples reported by Main & Weston. A rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 10 publications
1
11
0
2
Order By: Relevance
“…We conclude, therefore, that the BNPI has shown potential to be used in other studies and in clinical practice because it was understandable and showed consistent results in all items when administered to Brazilian mothers of healthy full-term newborns, who had pregnancies with no complications. Our results were similar to those found for other populations from the USA (19)(20)(21) , Sweden (22,23) , and Australia (24,25) . Based on these findings, it might be interesting to expand the use of this inventory and administer it to Brazilian mother-infant dyads at risk of having problems to establish a bond, such as teenage mothers, mothers of premature infants, assisted reproduction mothers, and mothers of twins.…”
Section: Discussionsupporting
confidence: 92%
“…We conclude, therefore, that the BNPI has shown potential to be used in other studies and in clinical practice because it was understandable and showed consistent results in all items when administered to Brazilian mothers of healthy full-term newborns, who had pregnancies with no complications. Our results were similar to those found for other populations from the USA (19)(20)(21) , Sweden (22,23) , and Australia (24,25) . Based on these findings, it might be interesting to expand the use of this inventory and administer it to Brazilian mother-infant dyads at risk of having problems to establish a bond, such as teenage mothers, mothers of premature infants, assisted reproduction mothers, and mothers of twins.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, these findings indicate the importance of attachment as a factor in dating aggression. However, while attachment insecurity is linked to violence, it cannot provide a sufficient explanation since insecure attachments are far too common (Broussard, 1995) and most individuals who have insecure attachment patterns do not become violent at all.…”
Section: Attachmentmentioning
confidence: 99%
“…Environmental factors associated with increased risk for both perinatal depression and disorganized infant-mother attachment include giving birth during adolescence, less education, and lower socioeconomic status (Broussard, 1995; Bunevicius et al, 2009; Cyr, Euser, Bakermans-Kranenburg, & van IJzendoorn, 2010; Spieker & Bensley, 1994; Troutman & Cutrona, 1990). …”
Section: Discussionmentioning
confidence: 99%